Studi atas Kualitas Jasa Sistem Informasi pada Bisnis E-Voucher - Pepie Diptyana; Stefy Agnestasia (Neo-Bis, 2010)
Service quality (servqual) in information system (IS) has been an interesting research topic recently. Various business types has emerged new dimensions of information system needs. IS servqual dimensions should be investigated through different kinds of business types.Previous studies has yield varying results. This research studies the effect of IS servqual dimension toward user satisfaction in e-voucher business. Data was collected from 108 respondents that are e-voucher reseller. There are five servqual dimensions: reliability, responsiveness, assurance, empathy, and tangibles. Tangible were excluded from test because IS provider does not facilitate hardware, employee, and any tangible asset to user. Based on regression result analysis, this research concluded that tested servqual dimensions has significantly influenced user satisfaction, unless assurance. This result shows that user satisfaction for business type that relied on IS as communication tool mostly influenced by reliability, responsiveness and empathy rather than assurrance. This might caused by However, further research needed to explore the usability of IS for reseller’s accounting data and to concern servqual dimension for another type of business and variable expansion also.